The Influence of the Student Facilitator and Explaining (SFAE) Learning Model on Critical Thinking Abilities and Geography Learning Outcomes of High School Students - Ulfa, Maria; Astutik, Sri; Susiati, Ana; Pangastuti, Era Iswara; Apriyanto, Bejo (Ruang Publikasi Ilmiah, 2024)
Students' low critical thinking skills will of course also affect their learning outcomes. This is influenced by the use of conventional learning models. This research aims to examine the influence of the Student Facilitator and Explaining (SFAE) model on students' critical thinking abilities and geography learning outcomes for high school students. This research was conducted experiments using a posttest only control group design. The research samples in the form of control and experimental classes were selected using the cluster random sampling method which had previously been tested for homogeneity via SPSS V.25 and was proven to be homogeneous. The data collection techniques used were critical thinking ability tests in the form of descriptions, geography learning outcomes tests in the form of multiple choice, observation, interviews and documentation. The data analysis techniques used are normality test, homogeneity test, hypothesis test, critical thinking ability data analysis and learning outcomes data analysis. Based on the research results, it shows that the Student Facilitator and Explaining (SFAE) learning model has a significant effect on students' critical thinking abilities based on the Independent Sample t-test with a significance value of 0.001 < 0.05 and also has a significant influence Influence on students' geography learning outcomes based on independent sample T-test with a significance value of 0.016 <0.05. This makes the Student Facilitator and Explaining (SFAE) learning model an alternative model that can be applied in schools to improve students' critical thinking skills and geography learning outcomes, especially high school students.